Comparison of Apixaban and Aspirin in Preventing Portal Vein Thrombosis after Laparoscopic Splenectomy for Cirrhotic Hypersplenism - Shi, Zhaobao; Xiao, Kunqing; Gao, Tianming; Jin, Shengjie; Zhang, Chi; Zhou, Baohuan; Bai, Dousheng; Jiang, Guoqing (Thrombosis and Haemostasis, 2024)
Portal vein system thrombosis (PVST) is a frequent and possibly fatal concurrent disorder following splenectomy. The optimal anticoagulant to prevent PVST following splenectomy remains unclear.The purpose of this study was to compare the safety and efficacy of apixaban versus aspirin in preventing PVST after laparoscopic splenectomy (LS) for cirrhotic hypersplenism.In this single-center randomized controlled trial, 80 patients with liver cirrhosis who received LS were randomly allocated to two treatment arms that were treated with apixaban or aspirin for 6 months. The primary effectiveness outcome was PVST formation after LS.We excluded four patients who withdrew from the study. The dynamic incidence of PVST, main and intrahepatic branches of PVST, and splenic vein thrombosis in the 6 postoperative months were all significantly lower in the apixaban treatment arm compared to the aspirin treatment arm (all P <0.001). Significantly lower incidences of PVST, main and intrahepatic branches of PVST, and splenic vein thrombosis in apixaban treatment arm started from postoperative day 7, month 1, and day 7 compared to the aspirin treatment arm respectively (all P <0.05). Multiple logistic regression analysis revealed that apixaban was an independent protective factor for PVST at postoperative month 3, as compared with aspirin (relative risk, 0.057; 95% confidence interval, 0.013–0.248; P <0.001).Compared with aspirin, apixaban could earlier and more effectively prevent PVST following LS for cirrhotic hypersplenism. Apixaban can be chosen as a priority treatment option versus aspirin, contributing to a lower risk of PVST.
Keywords: apixaban; aspirin; laparoscopic splenectomy; thrombosis; portal hypertension